Perceived parental involvement and social self-concept of tertiary institution students in Osun State, Nigeria - Omoyemiju, Michael Adeniyi; Nkachukwu, Hope Njideka (American Journal of Education and Learning, 2023)
This study examined the level of social self-concept and perceived parental involvement of tertiary institution students in Osun State. It also looked into the correlation between perceived parental involvement and the social self-concept of students. The descriptive survey design was adopted for the study. The study population comprised all the students in the tertiary institution in Osun State. A total sample of 1,440 students was selected using a multi-stage sampling procedure. An instrument titled “Questionnaire on Perceived Parental Involvement and Social Self-Concept (QPPISSC)” was utilized to collect data. Data gotten were analysed using frequency counts, percentages, stepwise multiple regression analysis, point bi-serial correlation, and Pearson product-moment correlation analysis. The results showed that 69.6% of tertiary institution students in the state exhibited a high level of social self-concept while 28.8% and 1.7% exhibited moderate and low levels of social self-concept respectively. Also, a statistically significant relationship was found between perceived parental involvement and the social self-concept of tertiary institution students (r = 0.526, p < 0.05). The study concluded that the social self-concept of tertiary institution students in Osun State was high and that perceived parental involvement, locus of control, institution type and age were potent factors that could positively predict the social self-concept of students. The study recommended that any counselling intervention to be implemented by professional helpers should not be age bias.